Dialectal Divergence in Alorese: Evidence from Lexical, Phonological, and Morphological Variation across Alor and Pantar - Sulistyono, Yunus (Masyarakat Linguistik Indonesia, 2025)
This paper investigates the dialectal divergence within Alorese, an Austronesian language spoken across the Alor and Pantar islands in eastern Indonesia. Based on primary fieldwork conducted in 2018 and 2020, this study analyzes lexical, phonological, and morphological data collected from 13 Alorese-speaking villages. The primary aim is to determine whether the language varieties spoken on Alor and Pantar constitute distinct dialects, and to identify the linguistic features that define them. The analysis reveals consistent patterns of variation: eastern Alor varieties exhibit conservative phonological traits, such as the retention of Proto-Alorese *f and the use of glottal stops, while Pantar varieties display innovations including *f > w and morphophonological restructuring. Morphologically, personal pronouns and demonstratives differ systematically between the two groups, with Pantar showing greater diversity and borrowing from Indonesian. Lexically, several key items, such as terms for all, many, and person, reflect parallel divergence. These linguistic patterns correlate with geographic distribution, historical trade routes, and sociolinguistic contact, particularly with Papuan and Malay-speaking populations. The findings provide robust evidence for distinguishing between the Alor and Pantar dialects of Alorese and contribute to broader discussions of dialect formation and contact-driven change in eastern Indonesia.